Krisis Demokrasi dan Tirani Meritokrasi Menurut Michael Sandel - Otto Gusti Madung (Institut Filsafat dan Teknologi Kreatif Ledalero, 2020)
This article aims to introduce the basic thesis of Michael Sandel as described in the book the Tyranny of Merit about the link between the contemporary crisis of democracy and meritocracy. The crisis of democracy today is shown through the increasing wave of right-wing populism in some democratic countries in Europe and the USA. According to Michael Sandel, the crisis of democracy is caused by the policy of meritocracy launched by the liberal democracy that has marginalized the groups of the middle class and working class. Furthermore, the article argues that populist leaders such as Donald Trump succeed in capitalizing on the grievances and frustration of social groups and expressing them as a political agenda. Based on the communitarianism of Michael Sandel, this article offers a solution to strengthen the role of social solidarity and community to cope with individualism and the crisis of liberal democracy. Key words: Crisis of democracy, meritocracy, liberalism, communitaranism, Michael Sandel.